2022
DOI: 10.14336/ad.2022.01281
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability, Dysbiosis, Inflammation and Enteric Glia Cells: The Intestinal Etiology of Parkinson’s Disease

Abstract: The scientific and medical communities are becoming more aware of the substantial relationship between the function of the central nervous system (CNS) and the state of the gut environment. Parkinson's disease (PD) is a neurodegenerative disorder that affects the nigrostriatal pathway in the midbrain, presenting not only motor symptoms but also various non-motor manifestations, including neuropsychiatric symptoms and gastrointestinal (GI) symptoms. Over time, our knowledge of PD has progressed from the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…However, the hypothesis that the enteric glia is affected by ZIKV infection in vivo, as well as the possible consequences of this infection, have yet to be demonstrated. Of note, accumulating evidence has revealed that GI disorders are possible pathological initiators of PD many years before it progresses to the CNS, with an important role for enteric glial cells (Yang et al, 2022).…”
Section: Glial Cells As Targets Of Zikv Infectionmentioning
confidence: 99%
“…However, the hypothesis that the enteric glia is affected by ZIKV infection in vivo, as well as the possible consequences of this infection, have yet to be demonstrated. Of note, accumulating evidence has revealed that GI disorders are possible pathological initiators of PD many years before it progresses to the CNS, with an important role for enteric glial cells (Yang et al, 2022).…”
Section: Glial Cells As Targets Of Zikv Infectionmentioning
confidence: 99%
“…Recent studies have provided evidence that PD results from an alteration in the gut microbiota, characterized by changes in gut permeability due to an increase in pathogenic bacteria [ 31 ]. Compared to the Saline + Vehicle group, the MPTP + Vehicle group showed increased expression of the proinflammatory cytokines IL-12a in mice, although it showed no significant difference in expression.…”
Section: Resultsmentioning
confidence: 99%
“…Gastrointestinal disorders and inflammation commonly occur in PD patients [ 44 ]. To demonstrate the effect of FMT from PD patients and healthy human controls on the colon in MPTP-treated mice, we tested inflammation in the gut via H&E staining, immunofluorescence and western blotting.…”
Section: Resultsmentioning
confidence: 99%